Technical Assistance in Identifying and Structuring Slum Infrastructure in Danukusuman Area, Serangan, Surakarta City - Sartika Nisumanti; Khodijah Al Qubro; Yessi Khairunnisa; Muhammad Rafi Kenedi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Surakarta is a city located in Central Java province and is one of the largest cities in Central Java Province. The high population density will be a problem in the future that needs to be considered. The slums in Surakarta city are scattered in several urban villages including the slum area is Danukusuman area of 8,178 Ha, It consists of Danukusuman Village covering 1,173 Ha, Joyotakan Village covering 5,753 Ha, and Pasar Kliwon Village covering 1,252 Ha. The typology of the Danukusuman area is a slum area located on the banks of the Bengawan Solo River with buildings that are classified as illegal. On the other hand, this area faces quite complex problems including unorganized housing conditions, narrow neighborhood roads, poor drinking water supply and sanitation conditions, poor drainage systems and lack of provision of other infrastructure facilities. This community service aims to identify slums so as to obtain slum characteristics and the level of slums. In addition, it makes a plan for infrastructure arrangement. The method is done through observation and scoring based on slum identification standards. The results obtained in this Community Service are the characteristics of slums and the level of slums and the design of infrastructure arrangement planning in the Danukusuman area.